The optimization of an accomodation in the thoracic cavity child the axial pump don-3 (the mathematical model research) - V. A. Kozlov; O. Yu. Dmitrieva; G. P. Itkin; A. S. Ivanov; A. P. Kuleshov; E. A. Volkova; T. N. Govorova (Вестник трансплантологии и искусственных органов)
We have developed and tested a technique for constructing 3D models of the chest and thoracic cavity organs. Due to the obtained results, the mathematical model  was successfully used in the development of classification of variants of placement  of implantable auxiliary circulation systems, and also for building 3D models for  other purposes. In particular, the patients were graded according to the variants of  placing the children’s axial pump DON-3 inside the patient’s chest cavity. Based on  the data, the first fitting of the DON-3 pump was performed on a patient aged 7 years.